(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study sought to assessthe adequacy of business education curriculum content for the acquisition of office technology and management and entrepreneurship skills acquisition in colleges of education in Edo and Delta States. Two research questions were raised and four null hypotheses were tested. Descriptive survey research was adopted for the study. The entire population of 120 business educators were studied without sampling. A structured and validated two-point checklist was used for data collection. Since, the National Commission for Colleges of Education (NCCE) Benchmark inventory is a standard checklist, the checklist was not subjected to reliability procedures because the checklist is already validated and standardized. Mean and standard deviation were used to answer the research question,’while ttest and Analysis of Variance (ANOVA) were used to test the null hypotheses. Findings of the study revealed that 68 contents of the curriculum are adequate and 46 contents are not adequate for the acquisition of office technology and management skills. 11 contents of business education curriculum are adequate and four contents are not adequate for the acquisition of entrepreneurship skills. The study further disclosed that bbusiness educators based on their years of experience and location did not differ significantly on their mean ratings on the adequacy of business education curriculum content for the acquisition of office technology and management skills and entrepreneurship skills among students. It was recommended among others that business educators in Colleges of education should periodically invite office technology and management experts and successful entrepreneurs to provide business education students with first hand business experiences and practical workplace skills required in the business world.